2016
DOI: 10.1073/pnas.1603271113
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between RNA polymerase and the core recognition element are a determinant of transcription start site selection

Abstract: During transcription initiation, RNA polymerase (RNAP) holoenzyme unwinds ∼13 bp of promoter DNA, forming an RNAP-promoter open complex (RPo) containing a single-stranded transcription bubble, and selects a template-strand nucleotide to serve as the transcription start site (TSS). In RPo, RNAP core enzyme makes sequence-specific protein-DNA interactions with the downstream part of the nontemplate strand of the transcription bubble ("core recognition element," CRE). Here, we investigated whether sequence-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…The discriminator region between the −10 hexamer and the transcription start site (TSS; +1) has recently emerged as an important modulator of the open complex properties (11)(12)(13)(14)(15)(16)(17)(18). In a stable open complex formed by Thermus thermophilus RNAP, the −6 and −5 bases of the discriminator NT strand (NT DISC ) make crucial contacts with σ1.2, and βArg371 (E. coli numbering) interacts with the adjacent −4 and −3 bases (14).…”
Section: Resultsmentioning
confidence: 99%
“…The discriminator region between the −10 hexamer and the transcription start site (TSS; +1) has recently emerged as an important modulator of the open complex properties (11)(12)(13)(14)(15)(16)(17)(18). In a stable open complex formed by Thermus thermophilus RNAP, the −6 and −5 bases of the discriminator NT strand (NT DISC ) make crucial contacts with σ1.2, and βArg371 (E. coli numbering) interacts with the adjacent −4 and −3 bases (14).…”
Section: Resultsmentioning
confidence: 99%
“…Promoter recognition is thought to be mediated by sigma factor-DNA interaction and core promoter elements comprising Ϫ35, Ϫ10, and extended Ϫ10 regions (12,23); however, a high-resolution study of an open promoter complex with Thermus thermophilus holoenzyme recently revealed the presence of a new determinant called the core recognition element (CRE) that is thought to provide sequence-specific promoter recognition of the Ϫ4 to ϩ2 region of the nontemplate DNA strand (89). Additional studies in E. coli have extended these findings and shown that the CRE can modulate transcription start site selection, elongation, and pausing and that mutation of the CRE impairs transcription (88,97).…”
Section: Discussionmentioning
confidence: 99%
“…MASTER has been used to define, comprehensively, critical sequence determinants for transcription start site selection, reiterative transcription initiation, and transcript yields for E. coli RNAP (Winkelman et al, 2016; Vvedenskaya et al, 2016; Vvedenskaya et al, 2015; Hochschild, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, for a given promoter sequence variant, the sequence of RNA 5' ends generated from the sequence variant defines the positions where transcription start site selection occurs for this promoter sequence [see (Vvedenskaya et al, 2018; Vvedenskaya et al, 2016; Vvedenskaya et al, 2015; Winkelman et al, 2016)] and can be used to define the extent of reiterative transcription initiation (“slippage synthesis”) for this promoter sequence (Vvedenskaya et al, 2015)…”
Section: High-throughput Sequencing Of Rna 5' Ends (5' Rna-seq)mentioning
confidence: 99%